ANALISIS PENGARUH LAJU INJEKSI CO2 KONTINU DAN IMPURITAS TERHADAP RECOVERY FACTOR LAPANGAN DF - dheafilla-02; Sari, Riska Laksmita (JSED, 2025)
This study focuses on evaluating the impact of varying continuous CO₂ injection rates and CO₂ impurity contents, such as N₂ and CH₄, on the Recovery Factor (RF) in the DF Field. Simulations were conducted using reservoir simulation with CO₂ injection rates of 1.3 MMSCFD, 2 MMSCFD, 3 MMSCFD, and 4 MMSCFD, as well as variations in CO₂ impurity mixtures, namely CO₂ 90% + N₂ 10%, CO₂ 90.1% + CH₄ 9.9%, and CO₂ 89.8% + N₂ 5.1% + CH₄ 5.1%. The results show that increasing the CO₂ injection rate is directly proportional to an increase in the recovery factor, with the highest recovery factor of 22.00% achieved in the 4 MMSCFD injection scenario. The effect of CO₂ impurities is evident in the scenario with N₂, which increases the Minimum Miscibility Pressure (MMP), potentially reducing sweep efficiency, while CH₄ has a moderate effect on the recovery factor and does not significantly reduce efficiency. The combination of CO₂ + N₂ yields the highest recovery factor at a 4 MMSCFD injection rate, reaching 17.00%. These results indicate that selecting the appropriate injection rate and controlling CO₂ impurities play a crucial role in enhancing oil production in heterogeneous reservoirs. The conclusion of this study is that choosing the optimal injection scenario can significantly improve oil recovery while minimizing operational risks related to sweep efficiency and fluid mobility in the reservoir.